A Case Series on the Devastating Simultaneous Bilateral Fracture of Ankles That Remains Under-reported: Can We Address the Career-Ending Injuries? - Thabo Leonard Muhango; Thandile Savanna Cordes; Collen Sandile Nkosi; Mmampapatla Thomas Ramokgopa (Journal of Orthopaedic Case Reports)
Introduction: Bilateral simultaneous rotational ankle fractures are an unusual phenomenon that remains unreported in the English literature, and to our knowledge, about 10 cases have been reported. The aim of the study was to evaluate and report clinical outcomes of bilateral simultaneous ankle fractures in our institution. Case Reoprt: We conducted a review of our 2-year experience with patients who had simultaneous bilateral fractures of the ankles and were treated at our institution. The included patients underwent surgical treatment using open reduction and internal fixation. Patients’ functional outcomes were assessed using patient-reported outcome measures (PROMs), namely the Short Form-36 questionnaire and the Olerud and Molander Ankle Outcome Score (OMAS). Results: Two cases (four ankles) of simultaneous bilateral rotational ankle fractures were identified in our institution’s records. Both cases involved a pedestrian motor vehicle accident. They were both female and had an average age of 22.5 years. Due to an open injury, one ankle underwent a staging procedure, and the other three underwent open reduction and internal fixation with excellent clinical outcomes. Functional outcomes were measured with PROMs. Conclusion: Simultaneous bilateral ankle fractures, while uncommon, can have a substantial impact on an individual’s mobility and health-related quality of life. Early surgical intervention and effective rehabilitation enhance functional results in this devastating journey.